2023
DOI: 10.1136/bmjresp-2023-001850
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of collagen XIII to lung function and development of pulmonary fibrosis

Oula Norman,
Jarkko Koivunen,
Riitta Kaarteenaho
et al.

Abstract: BackgroundCollagen XIII is a transmembrane collagen associated with neuromuscular junction development, and in humans its deficiency results in congenital myasthenic syndrome type 19 (CMS19), which leads to breathing difficulties. CMS19 patients usually have restricted lung capacity and one patient developed chronic lung disease. In single-cell RNA sequencing studies, collagen XIII has been identified as a marker for pulmonary lipofibroblasts, which have been implicated in the resolution of pulmonary fibrosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The most highly expressed TGF-β subtype in the human airway is transforming growth factor beta-1 (TGF-β1), which is known as a brogenic factor, a powerful inducer of collagen synthesis, and an important mediator of extracellular matrix formation. They have a direct impact on the collagen deposited in the airway wall, which encourages the development of brosis [23][24][25]. TGF-β1 regulates collagen breakdown in MMPs and TIMPs and plays a crucial role in airway remodeling through TGF-β1/Smad and NF-κb-class signaling pathways [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most highly expressed TGF-β subtype in the human airway is transforming growth factor beta-1 (TGF-β1), which is known as a brogenic factor, a powerful inducer of collagen synthesis, and an important mediator of extracellular matrix formation. They have a direct impact on the collagen deposited in the airway wall, which encourages the development of brosis [23][24][25]. TGF-β1 regulates collagen breakdown in MMPs and TIMPs and plays a crucial role in airway remodeling through TGF-β1/Smad and NF-κb-class signaling pathways [24].…”
Section: Introductionmentioning
confidence: 99%
“…They have a direct impact on the collagen deposited in the airway wall, which encourages the development of brosis [23][24][25]. TGF-β1 regulates collagen breakdown in MMPs and TIMPs and plays a crucial role in airway remodeling through TGF-β1/Smad and NF-κb-class signaling pathways [24]. McAlinden et al found that TGF-β1 inhibits autophagy and promotes the formation and deposition of ECM in myo broblasts, leading to enhanced brotic signaling [26].…”
Section: Introductionmentioning
confidence: 99%
“…The most highly expressed transforming growth factor beta (TGF-β) subtype in the human airway is TGF-β1, which is known as a brogenic factor, a powerful inducer of collagen synthesis, and an important mediator of extracellular matrix formation. TGF-β1 expression has a direct impact on the collagen deposited in the airway wall, which encourages the development of brosis [23][24][25]. TGF-β1 regulates collagen breakdown along with MMPs and TIMPs and plays a crucial role in airway remodeling through the TGF-β1/Smad and NF-κb-class signaling pathways [24].…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β1 expression has a direct impact on the collagen deposited in the airway wall, which encourages the development of brosis [23][24][25]. TGF-β1 regulates collagen breakdown along with MMPs and TIMPs and plays a crucial role in airway remodeling through the TGF-β1/Smad and NF-κb-class signaling pathways [24]. McAlinden et al found that TGF-β1 inhibits autophagy and promotes the formation and deposition of ECM in myo broblasts, leading to enhanced brotic signaling [26].…”
Section: Introductionmentioning
confidence: 99%